Theory into Practice: Information Behavior in Pre‐Service Education for Information Service Roles. Issue 1 (13th October 2021) - VanScoy, Amy; Julien, Heidi; Harding, Alison
Abstract: This poster will present the results of an online survey of instructors of reference and information services courses in North American programs preparing information service professionals for practice. The survey explores instructors' decisions about incorporating information behavior theories, models, and concepts into their courses, as well as their perspectives on the appropriate balance between theoretical and practical course content. The survey constitutes phase three of a study with two previous phases: a content analysis of course syllabi for these courses and interviews with course instructors. Study results to date show that variation in instructors' information behavior expertise, and in their discretion to modify course content, lead to significant disparity in theory content. The findings suggest opportunities to educate course instructors in information behavior content, and to strengthen theoretical content in courses, which would better prepare future information service professionals to provide more effective service.